Redescription of the milliped Amphelictogon subterraneus bahamiensis Chamberlin, 1918, with an assessment of the family Chelodesmidae in the Bahamas (Polydesmida: Leptodesmidea) - Shelley, Rowland M. (Zootaxa, 2003)
The milliped Amphelictogon subterraneus bahamiensis Chamberlin, 1918, the only representative of the family Chelodesmidae in the Bahamas and the only one in the New World occurring in part north of the Tropic of Cancer, is recorded from Eleuthera Island in addition to published localities from Andros and Cat Islands, Bahamas, and Cayo Coco, Cuba, where it is common. A redescription in English is provided along with gonopod drawings in medial and lateral views; a female cyphopod is illustrated for the first time. The populations on these three Bahamian islands probably represent isolated fragments of a once continuous population on the Pleistocene “super-island” on Great Bahama Bank, which in turn likely originated through rafting from the area of Cuba that now includes Cayo Coco. Investigations are needed to learn whether the species still survives on Andros, Eleuthera, and Cat islands, and whether additional populations occur on other islands that were once joined in the Pleistocene land mass.